Cardiovascular disease risk factors in chronic kidney disease: A systematic review and meta-analysis. - Rupert W Major; Mark R I Cheng; Robert A Grant; Saran Shantikumar; Gang Xu; Issaam Oozeerally; Nigel J Brunskill; Laura J Gray (PLoS ONE)
Background and objectives Chronic kidney disease (CKD) is a global health burden and is independently associated with increased cardiovascular disease risk. Assessment of cardiovascular risk in the general population using prognostic models based on routinely collected risk factors is embedded in clinical practice. In CKD, prognostic models may misrepresent risk due to the interplay of traditional atherosclerotic and non-traditional risk factors. This systematic review's aim was to identify routinely collected risk factors for inclusion in a CKD-specific cardiovascular prognostic model. Design, setting, participants and measurements Systematic review and meta-analysis of observational cohort studies and randomized controlled trials. Studies identified from MEDLINE and Embase searches using a pre-defined and registered protocol (PROSPERO ID-2016:CRD42016036187). The main inclusion criteria were individuals ≥18 years of age with non-endstage CKD. Routinely collected risk factors where multi-variable adjustment for established cardiovascular risk factors had occurred were extracted. The primary outcome was fatal and non-fatal cardiovascular events. Results The review of 3,232, abstracts identified 29 routinely collected risk factors of which 20 were presented in more than 1 cohort. 21 cohorts were identified in relation to 27,465 individuals and 100,838 person-years. In addition to established traditional general population cardiovascular risk factors, left ventricular hypertrophy, serum albumin, phosphate, urate and hemoglobin were all found to be statistically significant in their association with future cardiovascular events. Conclusions These non-traditional risk factors should be assessed in the development of future cardiovascular prognostic models for use in individuals with CKD.